2011
DOI: 10.4093/dmj.2011.35.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Glycemic, Blood Pressure, and Lipid Control according to Education Types

Abstract: BackgroundDiabetes self-management education and reinforcement are important for effective management of the disease. We investigated the effectiveness of interactive small-group education on glycemic, blood pressure, and lipid levels.MethodsFor this study, 207 type 2 diabetes patients with suboptimal glycemic control (HbA1c levels >6.5%) were enrolled. The conventional education group received an existing education program from April to November in 2006, and the interactive education group received a new smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another problem is that we failed to show the efficacy of either intensive education or follow-up education. It has been reported that the type of education can cause differences in diabetes control [16]. This discrepancy should be reevaluated in a larger study.…”
Section: Discussionmentioning
confidence: 91%
“…Another problem is that we failed to show the efficacy of either intensive education or follow-up education. It has been reported that the type of education can cause differences in diabetes control [16]. This discrepancy should be reevaluated in a larger study.…”
Section: Discussionmentioning
confidence: 91%
“…The reasons for this discrepancy may be due to the following differences: 1) intervention type and period (6 weeks, man to man intervention, vs. 10 months, web-based intervention); 2) ethnicity; 3) characteristic of subjects (non-diabetic overweight-obese adults, vs. men with IFG and T2DM); 4) confounding factors (not include dietary change, vs. include dietary change). Intervention type and contact frequency reportedly influence the response to a lifestyle intervention ( 38 , 39 ). Although data are not shown, BMI were more decreased in the intervention group subjects with T2DM (-0.28 kg/m 2 ) when compared to intervention group subjects with IFG (-0.06 kg/m 2 ) ( P =0.039).…”
Section: Discussionmentioning
confidence: 99%
“…DSME is an established tool for improving clinical outcomes, such as for insulin use and self-care performance [1], metabolic outcome (glycemic control or lipid control) [234], rate of chronic complications [1], and degree of depressive symptoms [5]. …”
Section: Introductionmentioning
confidence: 99%
“…With the global increase in the proportion of the elderly population, clinical management catering to the elderly with diabetes has become increasingly important not only for pharmacologic management but also for diabetes self-management education (DSME). DSME is an established tool for improving clinical outcomes, such as for insulin use and self-care performance [ 1 ], metabolic outcome (glycemic control or lipid control) [ 2 3 4 ], rate of chronic complications [ 1 ], and degree of depressive symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%